Should Public Pensions be Funded? - Hemming, Richard (IMF Working Papers; Working Paper ;, 1998)
This paper outlines some of the arguments for and against the funding of public pensions, with a view to establishing whether there is an economic basis for judging funding to be superior to pay-as-you-go (PAYG). It is argued that funding does not have a clear advantage, and the case for a shift from PAYG to funding is thus an uneasy one. There is nonetheless growing advocacy of funded public pensions as part of an ideal pension system, which raises more general issues about the role of the public sector in pension provision.